2020
DOI: 10.1111/syen.12445
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of wing polymorphism and genital asymmetry in the thread‐legged bugs of the tribe Metapterini Stål (Hemiptera, Reduviidae, Emesinae) based on morphological characters

Abstract: Wing polymorphism and asymmetric male genitalia are intriguing morphological phenomena occurring in insects. Among Emesinae, or thread‐legged bugs, the tribe Metapterini Stål exhibits these two interesting morphological attributes. Nonetheless, evolutionary interpretations of these phenomena cannot be put forward because phylogenetic hypotheses for Emesinae are lacking. Thread‐legged bugs are easily recognized among assassin bugs due to their elongated and seemingly delicate body. The tribe Metapterini has 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 48 publications
(86 reference statements)
0
31
0
Order By: Relevance
“…Genital asymmetry appears to be evolutionarily labile (like other morphological characteristics of animal genitalia) [18], with multiple transitions from symmetry to asymmetry across lineages [51][52][53][54]. In anablepid fishes, the transition from symmetry to asymmetry appears to have occurred twice: once in males after the evolution of the male gonopodium and again in females of the genus Anableps.…”
Section: Discussionmentioning
confidence: 99%
“…Genital asymmetry appears to be evolutionarily labile (like other morphological characteristics of animal genitalia) [18], with multiple transitions from symmetry to asymmetry across lineages [51][52][53][54]. In anablepid fishes, the transition from symmetry to asymmetry appears to have occurred twice: once in males after the evolution of the male gonopodium and again in females of the genus Anableps.…”
Section: Discussionmentioning
confidence: 99%
“…The genitalia is one of the most important and useful species‐diagnostic characters in insect systematics (Song & Bucheli, 2010), is one of the most important criteria to take taxonomic decisions, and it is particularly useful in Heteroptera species delimitations. In Reduviidae, there are still scattered studies documenting in detail the male and female genitalia, and even less employing such character system in phylogenetic analyses (Castro‐Huertas et al, 2018, 2021; Forero & Weirauch, 2012; Weirauch, 2008). Despite this, the genitalia offer ideal characters for phylogenetic analyses, providing information for resolving relationships at different taxonomic levels.…”
Section: Introductionmentioning
confidence: 99%
“…The weak point of these analyses is the poorly sample used for the Saicinae (Hwang & Weirauch, 2012; Weirauch, 2008; Weirauch & Munro, 2009). In addition, recent studies within the allied subfamily Emesinae showed that the genital characters could offer information to elucidate the relationships and limits to tribal, generic, and specific levels (Castro‐Huertas et al, 2018, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Various hypotheses about the evolution of genital asymmetries have been suggested, for example, ecological constraints, internal space constraints that favour asymmetric morphology of internal organs which secondarily affect genitalia, sexual selection via antagonistic coevolution, and sexual selection favouring asymmetry as a mechanical compensation for behavioural changes of the mating position [ 6 , 7 ]. While external copulatory organs in insects have often been subject to investigations concerning asymmetries and the evolution thereof [ 8 11 ], internal reproductive structures have received far less attention. Usually, insect male internal reproductive organs consist of paired (and bilaterally symmetric) mesodermal testes, a pair of lateral ducts, the vasa deferentia, which each contain an enlarged region to serve as a sperm reservoir (vesiculum seminalis), and a median ectodermal ductus ejaculatorius.…”
Section: Introductionmentioning
confidence: 99%